Socio-Economic Effects of National Park Governance and Management: Lessons from Post-Socialist Era Estonia - Henri Järv (MDPI AG, 2021)
Despite the significant increase in protected territory globally, there is a common understanding that the designation of protected areas alone does not guarantee their effectiveness nor halt the loss of biodiversity. In addition to biodiversity conservation, protected areas are expected to perform a number of other functions, such as provide ecosystem services and improve local socio-economic conditions. Therefore, the need to strive towards mixed, decentralized conservation management and stakeholder involvement is increasingly emphasized. Although there is limited research, it has been noted that protected areas have not served wider objectives effectively enough. The current study provides insight concerning socio-economic effects of different governance and management practices of protected areas based on perceptions of residents and stakeholders of five national parks of Estonia. It was found that conservation status has an important impact on local socio-economic conditions largely depending on governance and management practices, resulting in both, positive and negative effects. It was concluded that the centralization of nature conservation and the abolition of protected area administrations have led to a gradual distancing of nature conservation from local conditions and the population, causing concern about the preservation of the living environment.